Computer Modelling Of Structural Transformations Of Nanopores In Fcc Metals. - Starostenkov, M D|Markidonov, A V|Zakharov, P V. (Materials research foundations ;, 2019)
The book focuses on the effects of shock waves on vacancies and their clusters in fcc crystals. Keywords: Computer Modelling of Nanopores, Molecular Dynamics, Fcc Metals, Defect Structures in Crystals, Radiation Material Science, Nano-Engineering of Materials, Ultrasonic Treatment of Materials, Radiation Induced Defects, Vacancy Clusters, Shock Wave Effects, Radiation-Resistant Materials, Thermomechanical Processing, Energy Transfer Mechanism, Nanopore Nucleation, Nanopore Based Filters, Nanopore Based Detectors, Cooling Elements in Nano-Electronics.